NILAI-NILAI RELIGIUS DALAM NOVEL “API TAUHID” KARYA HABIBURRAHMAN El SHIRAZY - Lulu Mutamiroh (LPPM UNISDA, 2017)
Literature is the result of a portrait of human life in general. The result of human life portrait was modified in various forms literature both poetry and prose. Authors conducted research on novel